Devising an integrated methodology for energy safety assessment at an industrial power-generating enterprise - Prokhorova, Viktoriia; Budanov, Mykola; Budanov, Pavlo (Eastern-European Journal of Enterprise Technologies, 2024)
This paper’s research object is a process of estimating the level of energy safety at an industrial enterprise within an electricity-power system at a microeconomic level. The task to estimate the energy safety of an industrial enterprise was solved on the basis of a combined method for the continuous monitoring of threats under an automated mode to the hour, in order to make management decisions related to reducing the influence of threats to energy safety. Analysis of known methods for investigating the state of energy safety was performed, which revealed the lack of continuous control over the dynamic state of research objects, as well as the complexity in objectivity when giving exact and reliable primary information to calculate indicators-indexes. It has been shown that the use of the combined approach could underlie the development of methodology for estimating the energy safety of industrial power-generating enterprise. Such approach involves comprehensive combination of logical methods when implementing continuous monitoring of technological parameters at generation, transmission, distribution, and energy consumption facilities. The process of choosing the objects of research and criteria for describing their properties and functions has been substantiated, in order to build the system of indicators-indexes when estimating the level of enterprise energy safety. It has been shown that a computation algorithm makes it possible to monitor the dynamics of changes in indicators and take a management decision to eliminate energy safety threats, which leads to a reduction in economic losses in the amount exceeding USD 150,000. Practical significance of the current research relates to the fact that the results could be used by enterprises (public authorities) for determining obstacles on a way to reducing the consumption of power resources and devising a set of organizational-economic measures